Предмет: Алгебра,
автор: Adilzhan99
Решите уравнение: (5х – 3)(2х + 1) – (2х – 3)(5х + 4) = - 3
Ответы
Автор ответа:
0
(10x² - 6x + 5x - 3) - (10x² - 15x + 8x - 12) = -3
10x² - x -3 - 10x² + 7x +12 = -3
6x + 9 =-3
3(2x + 3) = -3
2x + 3 = -1
2x = -4
x = -2
Ответ: -2.
Автор ответа:
0
(10x² - 6x + 5x - 3) - (10x² - 15x + 8x - 12) = -3
10x² - x -3 - 10x² + 7x +12 = -3
6x + 9 =-3
3(2x + 3) = -3
2x + 3 = -1
2x = -4
x = -2
Похожие вопросы
Предмет: Английский язык,
автор: kirill1746
Предмет: Химия,
автор: emi200315
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Алгебра,
автор: 1981181
Предмет: Алгебра,
автор: rembomax